054 Tolerability of fremanezumab in migraine patients with cardiovascular medica- tion use at baseline: a pooled analysis. Issue 6 (27th May 2022) - Coppola, Gianluca; Cohen, Joshua; Ning, Xiaoping; Kessler, Yoel; Janka, Lindsay; Riaz, Sajjad; Barbanti, Piero
Abstract : Objective: To evaluate adverse events (AEs) in a subgroup of migraine patients with baseline cardiovas- cular (CV) medication use in this pooled analysis of three phase 3 trials of fremanezumab. Methods: This analysis included data from the HALO EM, HALO CM, and FOCUS studies, in which patients were randomized 1:1:1 to subcutaneous quarterly or monthly fremanezumab or matched placebo over 12 weeks. AEs were evaluated for patients with baseline CV medication use. Results: Overall, 280 of 2, 842 patients (9–11% across treatment groups) in this pooled population were receiving CV medications at baseline, most commonly agents acting on the renin-angiotensin system (3–4%) and beta-blockers (3–4%). In the placebo, quarterly fremanezumab, and monthly fremanezumab groups, respectively, 53%, 66%, and 64% of patients reported at least 1 AE, and the most common AEs were injection-site-related (pain [19%, 29%, and 20%], erythema [10%, 20%, and 13%], and induration [8%, 18%, and 24%]). Cardiovascular AEs (CVAEs) were infrequent; no individual CVAE was reported for >1 patient in any treatment group. No safety signals were identified. Conclusion: In this pooled analysis, fremanezumab treatment was well tolerated over 12 weeks, with low incidences of CVAEs, comparable to placebo, in patients with migraine using CV medications at baseline. JMarzella@cellohealth.com 52